(untitled) (Law Research Review Quarterly, 2026)
In the Indonesian criminal justice system, Visum et Repertum occupies a strategic position, especially in situations where children become victims of sexual violence, as it serves as evidence that provides medical and scientific support for proving the elements of a crime. This study aims to analyze the role of Visum et Repertum in proving criminal acts of sexual violence against children and its position as material for judges’ consideration in deciding cases, with a focus on Decision Number 652/Pid.Sus/2024/PN Btm. The research uses a normative legal method, combining a regulatory approach and case studies, which are then analyzed qualitatively. The results of the study show that based on Law Number 8 of 1981 concerning the Criminal Procedure Code, under Article 184 paragraph (1) in relation to Article 187 of the Criminal Procedure Code, Visum et Repertum constitutes documentary evidence within the criminal justice system. However, its probative force is not autonomous, as it must be considered alongside other admissible evidence and the judge’s conviction in accordance with Article 183. Accordingly, Visum et Repertum serves as a crucial instrument in supplying objective medical findings, particularly in cases concerning sexual abuse of children. With the enactment of Law Number 20 of 2025 concerning the Criminal Procedure Code, the evidence system has undergone improvements that further emphasize the position of documentary evidence in the criminal justice process. Thus, the Visum et Repertum serves not only as a medical document but also as a legal instrument supporting the realization of material truth and the principle of assisting the judge in forming an objective and measurable legal conviction.